Molecular detection of multidrug-resistant Mycobacterium leprae from Indian leprosy patients. (March 2018) - Lavania, Mallika; Singh, Itu; Turankar, Ravindra P.; Ahuja, Madhvi; Pathak, Vinay; Sengupta, Utpal; Das, Loretta; Kumar, Archana; Darlong, Joydeepa; Nathan, Rajeev; Maseey, Asha
Highlights: Detection of multidrug-resistant Mycobacterium leprae from relapse leprosy patients from endemic regions in India. Resistance profiles of strains to rifampicin, dapsone and ofloxacin were determined. Resistance confirmed by identification of mutations in genes earlier shown to be associated with resistance to each drug. Fifteen strains showed representative mutations in at least two drug resistance genes. Two strains showed mutations in all three genes responsible for resistance to rifampicin, dapsone and ofloxacin. Abstract: Objectives: The emergence of multidrug-resistant (MDR) organisms for any infectious disease is a public health concern. Global efforts to control leprosy by intensive chemotherapy have led to a significant decrease in the number of registered patients. Currently recommended control measures for treating leprosy with multidrug therapy (MDT) were designed to prevent the spread of dapsone-resistant Mycobacterium leprae strains. Here we report the identification of MDR M. leprae from relapse leprosy patients from endemic regions in India. Methods: Resistance profiles to rifampicin, dapsone and ofloxacin of the isolated strains were confirmed by identification of mutations in genes previously shown to be associated with resistance to each drug. Between 2009–2016, slit-skin smear samples were collected from 239 relapse and 11 new leprosy cases from hospitals of The Leprosy Mission across India. DNA was extracted from the samples and was analysed by PCR targeting the rpoB, folP and gyrA genes associated with resistance to rifampicin, dapsone and ofloxacin, respectively, in M. leprae . M. leprae Thai-53 (wild-type) and Zensho-4 (MDR) were used as reference strains. Results: Fifteen strains showed representative mutations in at least two resistance genes. Two strains showed mutations in all three genes responsible for drug resistance. Seven, seven and one strain, respectively, showed mutations in genes responsible for rifampicin and dapsone resistance, for dapsone and ofloxacin resistance and for rifampicin and ofloxacin resistance. Conclusion: This study showed the emergence of MDR M. leprae in MDT-treated leprosy patients from endemic regions of India.